Nor Syahirah attributes her success to consistent Dhuha and Tahajjud prayers - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) graduate, Nor Syahirah Mahmudin, 23 – one of this year’s recipients of the Yayasan Pahang Award at the university’s recent 14th Convocation – humbly attributed her secret to success to her consistent daily practice of the voluntary Islamic prayers of Dhuha and Tahajjud.